A Systematic Review of the Effects of Neuromodulation on Eating and Body Weight: Evidence from Human and Animal Studies. (20th September 2013) - McClelland, Jessica; Bozhilova, Natali; Campbell, Iain; Schmidt, Ulrike
Abstract: Background: Eating disorders (ED) are chronic and sometimes deadly illnesses. Existing treatments have limited proven efficacy, especially in the case of adults with anorexia nervosa (AN). Emerging neural models of ED provide a rationale for more targeted, brain‐directed interventions. Aims: This systematic review has examined the effects of neuromodulation techniques on eating behaviours and body weight and assessed their potential for therapeutic use in ED. Method: All articles in PubMed, PsychInfo and Web of Knowledge were considered and screened against a priori inclusion/exclusion criteria. The effects of repetitive transcranial magnetic stimulation (rTMS), transcranial direct current stimulation, vagus nerve stimulation (VNS) and deep brain stimulation (DBS) were examined across studies in ED samples, other psychiatric and neurological disorders, and animal models. Results: Sixty studies were identified. There is evidence for ED symptom reduction following rTMS and DBS in both AN and bulimia nervosa. Findings from studies of other psychiatric and neurological disorders and from animal studies demonstrate that increases in food intake and body weight can be achieved following DBS and that VNS has potential value as a means of controlling eating and inducing weight loss. Conclusions: Neuromodulation tools have potential for reducing ED symptomatology and related behaviours, and for altering food intake and body weight. In response to such findings, and emerging neural models of ED, treatment approaches are highly unlikely to remain 'brainless'. More research is required to evaluate the potential of neuromodulation procedures for improving long‐term outcomes in ED. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.